East–West Reverse Coupling Between Spring Soil Moisture and Summer Precipitation and Its Possible Responsibility for Wet Bias in GCMs Over Tibetan Plateau. Issue 7 (5th April 2022) - Yang, Kai; Wang, Chenghai
Abstract: The impact of soil moisture (SM) and precipitation coupling (SM‐P‐C) on the subsequent climate at daily to seasonal scales over the Tibetan Plateau (TP) is a critical issue. In this study, the spring SM and summer precipitation coupling (SSM‐SP‐C) were investigated using multi‐reanalysis and validated with 13 global climate models (GCMs) in Coupled Model Intercomparison Project Phase 5, and its relationship with the wet bias in GCMs was explored. The results reveal that SSM‐SP‐C shows an east–west reversal, with positive coupling in eastern and central TP and negative coupling in the western TP. The spring surface sensible heat has significantly negative effects on the strength of SSM‐SP‐C in eastern and central TP, while significantly positive effects in western TP; whereas, the SM shows the reverse effects in eastern and western TP. The concurrent SM‐P‐C over TP shows a positive trend from spring to summer, but coupling strength has significant spatial differences. The 13 GCMs ensemble mean underestimates the positive SSM‐SP‐C in eastern TP and can't reproduce the negative SSM‐SP‐C in western TP. The wet bias of summer precipitation is significantly associated with the model's failure in capturing SSM‐SP‐C. This study highlights the impacts of SM‐P‐C on subsequent climate in the alpine cold region and provides a potential way for reducing precipitation biases by improving SM‐P‐C parameterizations in GCMs. Key Points: Spring soil moisture and summer precipitation coupling (SSM‐SP‐C) shows an east‐west reversal, with positive coupling in eastern and central Tibetan Plateau (TP) and negative coupling in the western TP The SSM‐SP‐C has elevation‐dependent variations, the maximum coupling strength appears over regions with 3–4 km elevation Wet bias of summer precipitation is significantly associated with the model's failure in capturing SSM‐SP‐C